2020
DOI: 10.3390/microorganisms8101580
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms in Diabetic Foot Ulcers: Significance and Clinical Relevance

Abstract: Foot infections are the main disabling complication in patients with diabetes mellitus. These infections can lead to lower-limb amputation, increasing mortality and decreasing the quality of life. Biofilm formation is an important pathophysiology step in diabetic foot ulcers (DFU)—it plays a main role in the disease progression and chronicity of the lesion, the development of antibiotic resistance, and makes wound healing difficult to treat. The main problem is the difficulty in distinguishing between infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 123 publications
2
103
0
2
Order By: Relevance
“…Various studies have described the DFU microbiota to determine the role of microorganisms [ 33 ]. Although they have produced interesting results and confirmed that the microbiota is a highly dynamic microbial community that maintains a relationship with the host, better understanding of the complex competitive or synergistic interaction between commensal and/or pathogenic microorganisms is necessary as it could affect the severity and progression of the wound [ 7 ]. The virulence capacity of a bacterium has a direct impact on the equilibrium between colonization and infection [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have described the DFU microbiota to determine the role of microorganisms [ 33 ]. Although they have produced interesting results and confirmed that the microbiota is a highly dynamic microbial community that maintains a relationship with the host, better understanding of the complex competitive or synergistic interaction between commensal and/or pathogenic microorganisms is necessary as it could affect the severity and progression of the wound [ 7 ]. The virulence capacity of a bacterium has a direct impact on the equilibrium between colonization and infection [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we evaluated the role of a high glucose concentration and sub-MICs of two antibiotics in a WLM mimicking the conditions encountered in DFU on a series of clinical bacterial strains isolated from this clinical situation. To study bacterial virulence, most studies have previously used in vitro planktonic cultures on rich media or in vivo diabetes animal models (e.g., db/db mice), but without the ability to create genuine wound chronicity [ 7 ]. The WLM represents a convenient and reliable model to study bacteria in a relevant environment [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofilms also contribute to significant tissue destruction and sustained inflammation in diabetic wounds [ 203 ]. In addition to its potential role in early inflammation, reduced cathelicidin LL37 in diabetic wounds [ 194 ] may also contribute to biofilm control [ 204 ].…”
Section: Contribution Of Adipocytes To Impaired Wound Healingmentioning
confidence: 99%
“…The formation of different bacterial biofilms is shown in figure 6 (33) . Figure 6: the steps of the formation of bacterial biofilm (33) Neut and his coworker did a research in 2011 (34) , they reached evidences that shows the biofilms in DFU using a certain techniques and microscopes, this finding was confirmed by Malik and his coworkers in 2013 (35) who study more than 170 DFU cases, and they found around 70% of the cases under studies suffers from DFI (Diabetic Food Infection).…”
Section: The Significance Of Bacterial Biofilms In the Ulcers Foomentioning
confidence: 99%